2002
DOI: 10.1002/nml.12407
|View full text |Cite
|
Sign up to set email alerts
|

The Board as a Monitor of Organizational Activity: The Applicability of Agency Theory to Nonprofit Boards

Abstract: Despite the consensus about the significance of this crucial board responsibility, scholars know little about the ways in which a nonprofit board actually performs its monitoring function. In this article I report on an empirical study of the monitoring behavior of twelve nonprofit boards of directors. Agency theory provides the framework for this analysis. I show that the way in which individual board members define their relationship with the chief executive and understand the scope of the monitoring functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 17 publications
6
121
1
6
Order By: Relevance
“…In order to avoid these managerial opportunism practices (Miller, 2002), some mechanisms (financial rewards, shares) have been specified in order for the directorsto take into account the interests of the shareholders (Jensen & Meckling, 1976;Eisenhardt, 1989). According to the Agency Theory (Ross, 1973), solving the conflict between managers and shareholders (Magness, 2008) is quite important in order to come to an agreement about the companies' strategic decisions.…”
Section: Corporate Social Responsibility Financial Performance and Cmentioning
confidence: 99%
“…In order to avoid these managerial opportunism practices (Miller, 2002), some mechanisms (financial rewards, shares) have been specified in order for the directorsto take into account the interests of the shareholders (Jensen & Meckling, 1976;Eisenhardt, 1989). According to the Agency Theory (Ross, 1973), solving the conflict between managers and shareholders (Magness, 2008) is quite important in order to come to an agreement about the companies' strategic decisions.…”
Section: Corporate Social Responsibility Financial Performance and Cmentioning
confidence: 99%
“…A first explanation for the weak control by nonprofit boards might be drawn from Miller (2002). Her empirical research suggested that board members possess high confidence and trust in their management and make decisions based primarily on information provided by management and employees.…”
Section: Caers Du Bois Jegers De Gieter Schepers Pepermansmentioning
confidence: 99%
“…Still, as [12] notes, there is no basis to think that non-profit organizations are spared from "moral hazard, opportunism, adverse selection and other problems of asymmetric information". Agency theory framework can be applied to nonprofit organizations if some peculiarities of this sector are taken into consideration as shown several empirical and theoretical studies [11], [13], [14], [15], [16], [17]. More research is therefore needed.…”
Section: Agency Theory In Nonprofitmentioning
confidence: 99%
“…Principal-agent relations in non-profit organizations are even more problematic than in for-profit firms because of the lack of ownership incentives, complex and vague mission [15], lack of a single overriding objective [11] and even the absence of consensus on the identity of one single principal [14].…”
Section: Agency Theory In Nonprofitmentioning
confidence: 99%